Epidemiological, Clinical, and Paraclinic Aspect of Cutaneous Sarcoidosis in Black Africans - Mamadou Kaloga; Ildevert Patrice Gbéry; Vagamon Bamba; Yao Isidore Kouassi; Elidjé Joseph Ecra; Almamy Diabate; Sarah Kourouma; Kouadio Celestin Ahogo; Kouassi Alexandre Kouamé; Komenan Kassi; Kanga Kouame; Abdoulaye Sangaré (Hindawi Limited, 2015)
The specific objectives were to identify the epidemiology of cutaneous sarcoidosis and describe the clinical and laboratory aspects of the disease. Materials and Methods. We performed a descriptive cross-sectional study involving 24 referred cases of cutaneous sarcoidosis in 25 years (1990-2014) collected at Venereology Dermatology Department of the University Hospital of Treichville (Abidjan) both in consultation and in hospitalization. Results. The hospital frequency was one case per year. The average age was 42 years, ranging from 9 to 64. The sex ratio was 1. The shortest time interval between the appearance of the skin lesion and consultation of Dermatology Department at CHU Treichville was 3 months. The elementary lesions were represented primarily by a papule (18 cases), placard (3 cases), and nodule (2 cases) and mainly sat on the face and neck in 8 cases (38%). Extra cutaneous lesions were dominated by ganglion and respiratory involvement with 5 cases each followed by musculoskeletal damage in 3 cases. Chest radiography showed abnormality in 13 cases (54%). The pulmonary function test performed in 13 patients found 7 cases (54%) having restrictive ventilatory syndrome and 6 cases (46%) being normal. A tuberculin anergy was found in 11 cases (61%).